Supramolecular Halogen Bonds in Asymmetric Catalysis - Kaasik, Mikk; Kanger, Tõnis (Frontiers in Chemistry, 2020)
Halogen bonding has received a significant increase in attention in the past 20 years. An important part of this interest has centered on catalytic applications of halogen bonding. Halogen bond (XB) catalysis is still a developing field in organocatalysis, although XB catalysis has outgrown its proof of concept phase. The start of this year witnessed the publication of the first example of a purely XB-based enantioselective catalytic reaction. While the selectivity can be improved upon, there are already plenty of examples in which halogen bonds, among other interactions, play a crucial role in the outcome of highly enantioselective reactions. This paper will give an overview of the current state of the use of XBs in catalytic stereoselective processes.